Therapeutic Targeting of Oncogenic K‐Ras by a Covalent Catalytic Site Inhibitor1. Issue 1 (20th November 2013) - Lim, Sang Min; Westover, Kenneth D.; Ficarro, Scott B.; Harrison, Rane A.; Choi, Hwan Geun; Pacold, Michael E.; Carrasco, Martin; Hunter, John; Kim, Nam Doo; Xie, Ting; Sim, Taebo; Jänne, Pasi A.; et al.
Abstract We report the synthesis of a GDP analogue, SML‐8‐73‐1, and a prodrug derivative, SML‐10‐70‐1, which are selective, direct‐acting covalent inhibitors of the K‐Ras G12C mutant relative to wild‐type Ras. Biochemical and biophysical measurements suggest that modification of K‐Ras with SML‐8‐73‐1 renders the protein in an inactive state. These first‐in‐class covalent K‐Ras inhibitors demonstrate that irreversible targeting of the K‐Ras guanine‐nucleotide binding site is potentially a viable therapeutic strategy for inhibition of Ras signaling.